(untitled) (Medico Legal Update, 2020)
Background/Objectives: The study aimed to identify changes in dental plaque after intraoral application of a disclosing agent in two Qraycam groups and to investigate changes in oral health attitudes and behaviours. Method/Statistical Analysis: The study population consisted of 80 people who participated in the study between May and August 2019. The equipment used was Qraycam and a plaque control records (O’Leary index); oral health attitudes and behaviours were investigated. Differences in participant characteristics according to Qraycam use were analysed by ?2 test, while changes in the PCR(O’Leary index) by area for Qraycam use and non-use groups were analysed by pre-post paired-samples t-test. The influence on the oral health attitudes of the Qraycam use group was analysed by multiple linear regression analysis. All analyses were performed using IBM SPSS ver. 25.0 (IBM Co., Armonk, NY, USA) and the significance level for statistical testing was set to 0.05. Findings: In the Qraycam use group, a decrease in the PCR in the left and right sides showed statistically significant differences (p<0.05), while a change in the total PCR also showed a statistically significant difference (p<0.05), with the right side showing a greater change in dental plaque. In the Qraycam non-use group, there were no statistically significant differences in the decrease in the left, right, and total PCR. In the Qraycam-use group, the biggest influencing factor on oral health attitudes was oral health behaviour (p<0.05). Improvements/Applications: PCR(O’Leary index) decreased significantly in the Qraycam use group, influencing oral health education, attitudes, and behaviours. The active use of Qraycam for community-based oral health activities and clinical dentistry would assist oral health promotion.